Structural Shift with an Inter-Structural Transition Function - D.A. Wilton (Queen's University, Department of Economics, 1972)
The purpose of this paper is to suggest a simple model for the regression problem of a known switching date in structures which consumes several intervals of time to complete the shift. This model, then, permits a smooth transition from an old to a new structure, and is easily tested by employing standard t and F tests. Before presenting the model, a few examples of the type of economic problems for which this model is applicable will be discussed. First, the establishment of an Incomes Policy may take a number of time intervals to affect a change in the underlying structure (e.g, inflation expectations). Or, the price response of exporters and importers to a revaluation of a fixed foreign exchange rate may not occur simultaneously, but rather may be partially absorbed in profit margins over a transition period. Finally, corporation adjustments to a new industrial policy may be extended over a number of years. As illustrated in the present paper, the model is successfully applied to a structural shift problem of this latter variety arising from the signing of the Canada-U.S. Automotive Agreement.
Keywords: 330